EROSITA (eRASS1) study of the Canis Major overdensity: Developing a multi-wavelength algorithm for classifying faint X-ray sources - Saeedi, Sara; Sasaki, Manami; Knies, Jonathan; Robrade, Jan; Heindl, Theresa; Zainab, Aafia; Hämmerich, Steven; Reh, Martin; Wilms, Jörn (Astronomy & Astrophysics, 2024)
Context. Using data from eROSITA (extended Roentgen Survey with an Imaging Telescope Array) on board Spektrum-Roentgen- Gamma (Spektr-RG, SRG) taken during the first eROSITAall-sky survey (eRASS1), we performed the first X-ray classification and population study in the field of the Canis Major overdensity (CMa OD), which is an elliptical-shaped stellar overdensity located at l = -240°, b = -80°. Aims. This study aims to identify the X-ray sources in CMa OD. We developed a classification algorithm using multi-wavelength criteria as a preliminary method for the classification of faint X-ray sources, specifically in regions with a high source number density. Methods. We used the brightness of the multi-wavelength counterparts (mainly from infrared and optical catalogues), along with the X-ray flux and X-ray hardness ratios (HRs) to classify the sources. Results. Out of a total number of 8311 X-ray sources, we classified 1029 sources as Galactic stars and binaries in the foreground, 946 sources as active galactic nuclei (AGNs) and galaxies in the background, and 435 sources with stellar counterparts that may belong to either the MW or CMa OD. Among the sources with a stellar counterpart, we identified 34 symbiotic star candidates, plus 335 sources, of which the infrared (IR) counterparts have properties of M-giants in CMa OD. Moreover, there is a known high-mass X-ray binary (HMXB, 4U 0728-25) in the field of our study; according to the Gaia parallax of its companion, it appears to be a member of CMa OD. There is also a recently detected transient low-mass X-ray binary (LMXB, SRGt J071522.1-191609) is also present; it may be a member of CMa OD based on its companion, which is most likely highly absorbed and is thus located behind the Galactic disk. In addition, we present the X-ray luminosity function (XLF) of members and candidate members of CMa OD. It is dominated by sources with luminosities of <2 × 1032-1033 erg s-1 in the energy range of 0.2-2.3 keV. These sources are expected to be either accreting white dwarfs or quiescent LMXBs.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Binaries: symbiotic; Galaxies: dwarf; Galaxy: general; Novae; cataclysmic variables; X-rays: binaries; X-rays: galaxies

SRG/eROSITA 3D mapping of the interstellar medium using X-ray absorption spectroscopy - Gatuzz, E.; Wilms, Jörn; Zainab, Aafia; Freund, S.; Schneider, P. C.; Robrade, J.; Czesla, S.; García, J. A.; Kallman, T. R. (Astronomy & Astrophysics, 2024)
We present a detailed study of the hydrogen density distribution in the local interstellar medium (ISM) using the X-ray absorption technique. Hydrogen column densities were precisely measured by fitting X-ray spectra from coronal sources observed during the initial eROSITA all-sky survey (eRASS1). Accurate distance measurements were obtained through cross-matching Galactic sources with the third Gaia data release (DR3). Despite the absence of a discernible correlation between column densities and distances or Galactic longitude, a robust correlation with Galactic latitude was identified. This suggests a decrease in ISM material density in the vertical direction away from the Galactic plane. We have also investigated the relation between the optical extinction and the hydrogen column density. To do so, we employed multiple density laws to fit the measured column densities, revealing constraints on height scale values (9 < hz < 14 pc). Unfortunately, radial scales and the central density remain unconstrained due to the scarcity of sources near the Galactic center. Subsequently, a 3D density map of the ISM was computed using a Gaussian process approach, inferring hydrogen density distribution from hydrogen column densities. The results unveil the presence of multiple beams and clouds of various sizes, indicative of small-scale structures. High-density regions were identified at approximately 100 pc, consistent with findings in dust-reddening studies, and are potentially associated with the Galactic Perseus arm or the local bubble. Moreover, high-density regions were pinpointed in proximity to the Orion, Chameleon, and Coalsack molecular complex, enriching our understanding of the intricate structure of the local ISM.
CRIS-Team Scopus Importer:2024-09-06
Keywords: ISM: atoms; ISM: structure; Local insterstellar matter; X-rays: ISM

The giant outburst of EXO 2030+375: I. Spectral and pulse profile evolution - Thalhammer, Philipp; Ballhausen, R.; Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Zainab, Aafia; Staubert, R.; Pottschmidt, K.; Coley, Joel B.; Rothschild, R. E.; Jaisawal, G. K.; West, B.; Becker, P. A.; et al. (Astronomy & Astrophysics, 2024)
The Be X-ray binary EXO 2030+375 went through its third recorded giant outburst from June 2021 to early 2022. We present the results of both spectral and timing analysis based on NICER monitoring, covering the 2-10 keV flux range from 20 to 310 mCrab. Dense monitoring with observations carried out about every second day and a total exposure time of 160 ks allowed us to closely track the source evolution over the outburst. Changes in the spectral shape and pulse profiles showed a stable luminosity dependence during the rise and decline. The same type of dependence has been seen in past outbursts. The pulse profile is characterized by several distinct peaks and dips. The profiles show a clear dependence on luminosity with a stark transition at a luminosity of 2 × 1036 erg s-1, indicating a change in the emission pattern. Using relativistic raytracing, we demonstrate how anisotropic beaming of emission from an accretion channel with a constant geometrical configuration can give rise to the observed pulse profiles over a range of luminosities.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Stars: neutron; X-rays: binaries; X-rays: individuals: EXO 2030+375